ผลของการใช้หนังสืออิเล็กทรอนิกส์เสริมการเรียนรู้เรื่องการดูดเสมหะ ต่อผลสัมฤทธิ์การเรียน ความมั่นใจและความพึงพอใจของนักศึกษา - ผ่องอักษร ปานทิพย์; ศรีสอาด รตา; วงศ์ภมรมนตรี สิรินาถ (Journal of The Royal Thai Army Nurses, 2018)
งานวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาผลของการใช้สื่ออิเล็กทรอนิกส์เสริมการเรียนรู้เรื่องการดูดเสมหะในรายวิชาการพยาบาลพื้นฐาน ต่อผลสัมฤทธิ์การเรียน ความมั่นใจและความพึงพอใจของนักศึกษาพยาบาลชั้นปีที่ 2 วิทยาลัยเซนต์หลุยส์ กลุ่มตัวอย่างคือนักศึกษาพยาบาลชั้นปีที่ 2 ปีการศึกษา 2559 คณะพยาบาลศาสตร์ วิทยาลัยเซนต์หลุยส์ จำนวน 104 คน ทำการสุ่มอย่างง่ายโดยการจับคู่ (matched pair) ตามผลการเรียนให้ได้กลุ่มตัวอย่างเข้ากลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 52 คน กลุ่มทดลองได้รับการสอนโดยอาจารย์และเสริมการเรียนรู้ด้วยหนังสืออิเล็กทรอนิกส์ เรื่องการดูดเสมหะ ในขณะที่กล่มุควบคุม ได้รับการสอนโดยอาจารย์และเสริมการเรียนรู้ด้วยตนเอง เครื่องมือที่ใช้ในการวิจัยคือหนังสืออิเล็กทรอนิกส์ แบบประเมินความรู้ แบบประเมินปฏิบัติการดูดเสมหะ แบบวัดความมั่นใจในการปฏิบัติการดูดเสมหะ และแบบประเมินความพึงพอใจในการเรียนผลการวิจัยพบว่า 1) คะแนนเฉลี่ยความรู้หลังเรียนของกลุ่มทดลองมากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ(p < .05) 2) คะแนนเฉลี่ยปฏิบัติการดูดเสมหะของกลุ่มทดลองมากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ (p < .05) 3) คะแนนเฉลี่ยความมั่นใจปฏิบัติการดูดเสมหะของกล่มุ ทดลองมากกว่ากล่มุ ควบคุมอย่างมีนัยสำคัญทางสถิติ (p < .05) 4) คะแนนเฉลี่ยความพึงพอใจในการเรียนของกลุ่มทดลองมากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติ (p < .05)ผลการวิจัยนี้แสดงให้เห็นว่า หนังสืออิเล็กทรอนิกส์ช่วยเสริมการเรียนรู้ด้วยตนเองของนักศึกษา โดยช่วยเพิ่มทั้งความรู้และทักษะการดูดเสมหะ ทำให้นักศึกษามีความมั่นใจในการปฏิบัติการดูดเสมหะและพึงพอใจในการเรียน จึงควรนำหนังสืออิเล็กทรอนิกส์มาช่วยเสริมการเรียนรู้ของนักศึกษา เพื่อช่วยให้นักศึกษาได้เรียนรู้ตามศักยภาพและความต้องการของตนเอง The Result of Using Electronic Book to Enhance Suctioning on Achievement of Learning Outcome, Confidence and Satisfaction of Students The purpose of this study was to examine the achievement of learning outcome, confidence and satisfaction of students by using electronic book to enhance suctioning procedure. The samples of this study were a second-year nursing students who were studying Fundamentals of Nursing course of the academic year 2016 at Faculty of Nursing, Saint Louis College. The total of 104 samples were recruited in sample random sampling technique. Random assignment was used with matched-pair into two groups of experimental group and control group. Fifty-two students in the experimental group participated in a classroom lecture on topic of suctioning procedure and added up with electronic book as the learning material while the other fifty-two students in control group attended only classroom lecture on the topic of suctioning procedure and self-study. The study instruments were electronic book, knowledge test scale, suctioning procedure checklist, student satisfaction scale and student self-confidence scale. The findings of this study were as follow: 1) Paired t-test revealed significantly higher suctioning knowledge average scores in the post-test of experimental group compared to the control group (p-value<.05), 2) the mean scores on performing suctioning of experimental group was significantly higher than control group (p-value < .05), 3) the mean scores on self-confident to perform suctioning was significantly higher than control group (p-value < .001), and 4) the mean score of satisfaction on learning process of suctioning procedure was significantly higher than control group (p-value < .001). The results of this study indicate that an electronic book enhanced students on their self-study learning process of suctioning by increasing of both knowledge and skill of suctioning procedure. Therefore, the students have gained more of their self-confidence and student satisfaction about the performance of this procedure. As the result, the implication of the electronic book from this study could be helpful resources for improving the learning process regarding student competency and self-needs.